Reflections On The Theory Of Communication - Bojaxhi, Jola; Vrapi, Fatmir; Stojani, Edita (Advances in Social Sciences Research Journal, 2017)
From its very nature, language is dynamic. From the beginning of speech communication, language was shaped by different factors such as geographical populations movements, social and economic factors, political factors as well as development of technology that has influenced the spread and exchange of ideas. The aim of this paper is, to show how the language has evolved as well as how it has influenced communication between cultures. The methodology is descriptive by looking at different theories of communication. Nowdays, the fast development of technology is making a huge impact on the away we communicate with each other.